Advertisement and Sales Performance in Mtn Uganda, Kabale Branch. - Mwebesa, Acleo (Kabale University, 2023)
The study was to establish the effects of advertising on the sales performance of MTN Uganda, Kabale District. It was guided by a number of objectives, which were: to establish the various forms of advertisement used by MTN Uganda; to examine the effect of media advertisement on sales performance of MTN Uganda; to examine the effect of billboards and sponsoring events on sales performance of MTN Uganda; and to investigate the relationship between advertisement and sales performance of MTN Uganda in Kabale District. The data was collected from primary and secondary sources. The researcher used questionnaires and interview guides as research instruments. The study sample of 136 respondents was selected using simple random and purposive sampling. The respondents comprised employees of MTN Uganda, Kabale district, Qualitative data was analyzed using both descriptive and inferential statistics. Descriptive statistics included the use of frequencies and percentages to analyze biodata, while inferential statistics included the use of mean and standard deviations to test individual responses; as well as the Pearson correlation coefficient (r) to test the relationship between advertisement and sales performance of the MTN Uganda Kabale branch. The study findings revealed that the various forms of advertisement used by MTN Uganda included media, billboards, sponsorship of events, routine sales promotions, a website, and giving prizes with the company name. The results further revealed that there is no significant relationship between media advertisement and sales performance (r = 0.511, p = 0.663), there is a significant effect of billboards and sponsorship of events on sales performance (r = 0.003, p = 0.412), and lastly, there is no significant relationship between advertisement and sales performance of MTN Uganda Kabale district (r = 0.610, p = 0.713).Based on research findings, the following recommendations were made: there is a need for MTN Uganda to conduct a customer communication needs assessment and be in a better position to design a clear and dependable medium to reach out to the public with services and products; there is a need to hire marketing professionals with the ability to package advertisement messages; and there is a need to choose the right people and approach to deliver messages. While designing advertisement messages, there is a need to strike a balance between the message content, medium or channel used, and personal qualities of the people involved in the ads if the process is to be impactful. MTN, as a company, should invest in corporate social responsibility; this helps promote the company’s products and services while transforming customers’ lives and communities.